Sports participation as a social determinant of athletic sex differences - Whitten, Rebecca, author; Hempel, Lynn, advisor; Hastings, Pat, committee member; Daum, Courtenay, committee member (Colorado State University. Libraries, 2025)
The belief in a substantial gap in physical ability between men and women is one of the primary justifications for sex segregation in athletic competitions. However, limited attention has been paid to the gendered social forces that may be influencing these differences. This study asks whether gender differences in sports participation affect performance differences, examining high school track and field data covering 17 US states from 1979-2019 of state-level participation and corresponding state championship-winning performances across 5 events. Results show that for the 100m, 800m, 1600m, and pole vault, increased girls' participation predicts twice as much performance improvement as for boys, though no significant effects were found for high jump. Direct comparisons of gender gaps in participation to gender gaps in performance for each state show significant effects for the 100m (p<0.05), and no significant effects for the other four events. The findings suggest that increasing current participation levels of girls in high school track and field to equal boys' participation would decrease the gap in performance, though not erase it entirely, indicating that sports participation is one of multiple factors affecting gender differences in athletic performance. Based on these findings, I argue current sex differences in athletic abilities should not be attributed entirely to innate sex differences and that researchers should further consider the effects of social inequalities on sports participation and physical development.
Keywords: social determinants of athletic sex differences; athletic sex differences; sports participation